2021
DOI: 10.1136/bmjopen-2020-043795
|View full text |Cite
|
Sign up to set email alerts
|

Modelling palliative and end-of-life resource requirements during COVID-19: implications for quality care

Abstract: ObjectivesThe WHO estimates that the COVID-19 pandemic has led to more than 1.3 million deaths (1 377 395) globally (as of November 2020). This surge in death necessitates identification of resource needs and relies on modelling resource and understanding anticipated surges in demand. Our aim was to develop a generic computer model that could estimate resources required for end-of-life (EoL) care delivery during the pandemic.SettingA discrete event simulation model was developed and used to estimate resourcing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Our study period concluded in 2015, coinciding with the end of the economic recession in Spain. During this period, the efficient use of hospital services was of central importance, however, currently, the COVID pandemic requires additional physical and human resources at the end of life as part of the response to the pandemic ( Chalk et al, 2021 ). The COVID pandemic has most likely worsened the situation of patients such as those described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study period concluded in 2015, coinciding with the end of the economic recession in Spain. During this period, the efficient use of hospital services was of central importance, however, currently, the COVID pandemic requires additional physical and human resources at the end of life as part of the response to the pandemic ( Chalk et al, 2021 ). The COVID pandemic has most likely worsened the situation of patients such as those described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although our case study model is simple, the methods we describe are applicable across more complex simulations. To illustrate, our online Extended data 31 32 , renal 12 , stroke 33,34 , heart failure 35 , cancer care 36 , end of life care 13 , and operating theatre management 24,37 .…”
Section: Methodsmentioning
confidence: 99%
“…Free and Open Source Software (FOSS) for simulation offers an alternative to proprietary software without the licensing restrictions that affect uptake, sharing, and reuse of model code 10,11 . In health service delivery research, computational analyses, and simulation studies can be conducted using FOSS tools built in the popular coding languages of Python, R, and Julia [12][13][14][15][16][17] . Use of a language such as Python has further benefits for research as models can now be integrated with the wider data science ecosystem for statistical modelling and machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…44 This is not just for diagnostic and treatment services but palliative care services as well which were stretched during the pandemic and needs greater investment. 45 In addition, centralised control of NHS and private sector capacity is necessary to ensure cancer diagnostics and treatments can continue without delays and avoid the inequalities in management that have been observed nationally.…”
Section: Could Things Have Been Done Differently and Looking To The F...mentioning
confidence: 99%